PENGARUH BLENDEDDLEARNINGIBERBASISIMULTIIAPLIKASI UNTUK MENINGKATKAN HASILIBELAJARIMATEMATIKA PESERTA DIDIK SMPN 1 PADANG PANJANG - Zahara Ermanda Putri (Jurnal Edukasi dan Penelitian Matematika, 2021)
Learning result are benchmarks used toodetermineetheeleveloof successsof studentsiin understanding concepts in learning. But in fact, judging by the final assessment scores offtheeeighthhgrade mathematicians offSMPN 1 Padang Panjang for the 2020/2021 school year, it is still low. One effort that can overcome these problems is to use a multi-application-based blended learning model in the mathematics learning process. Theepurposeeoffthissstudy was toddetermine and describe the mathematics learning outcomes ofsstudentsswho study withtthe multi-application-based Blended Learning model at SMPN 1 Padang Panjang. This type of research is a pre-experimental research with the design of the one shot case study. The subjects of this study were students in class IX E of SMPN 1 PadanggPanjang in the 2021/2022 academic year. The instrument used is a test of mathematics learninggresult in the formoof description questions, theedata obtained are thenaanalyzed with the one sample tttest. Basedoonnthe analysis of the researchddata, ittcannbe seen thataat theereal level α = 0.05, P-value =00.000 is obtained for the data on mathematics learning result, because the P-value < α, then reject H0. sooittcannbeeconcludedtthattthe blendeddlearninggmodel hasaan effectoon learning result, where theelearning outcomes oftthose who learn withhthe blendedllearningamodel are better than theeresultsoof previous studies. Keywords – blended learning, learning result, One shot case study design